DEVELOPMENT OF CONCEPTION OF INCREASE OF EFFICIENCY WORKS OF DUG-OUTS OF GAS - Тимків, Дмитро Федорович; Костів, Ярослава Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article is dedicated to the development of the underground gas storage operation concept in Ukraine. The current state of underground gas storage the structure of its consumption is analyzed. It is found out that the gas storage system is concentrated unevenly in the gas supplying network of Ukraine. West complex of underground gas storage (UGS) is the most powerful in Ukraine, ensuring the reliability of gas supplies to Western and Eastern Europe. At the same time in other regions of Ukraine (Northern, Central, Eastern and Southern) there is a significant lack of capacity of underground gas storages. The author analyzed the workload indicators of OGS and made the appropriate calculations. At-market value of gas injection (selection) has been taken as the basic index of economic efficiency of UGS. It is summarized that in order to improve the efficiency of underground storage facilities it is necessary to make its reconstruction and shorten the time of gas extraction.